Implications of Participative Management as a Factor in Sustainable Performance: Analysis of Advantages and Forms of Management Approaches within Morocco’s SME’s - Sakhy, Chadi (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
The purpose of this analysis is to examine the competitive advantages that can be generated by the application of participative management within the organization. Among the many approaches and technologies that have been applied to date, some methods and technologies have proven to be unsuitable for the current economic and social environment. At the same time, organizations are always looking for more competitive resources to apply innovation and novelty in this field. Through the test model, the results of the analysis refer to data from 93 small and medium-sized companies and 86 in Morocco. In general, managers who adopt participatory and inclusive management practices such as strategic awareness and employee involvement in the implementation of organizational goals have better employee satisfaction and engagement, especially better employee performance and participation, ultimately giving the organization a competitive advantage.